2016
DOI: 10.1212/wnl.0000000000002841
|View full text |Cite
|
Sign up to set email alerts
|

Early diffusion evidence of retrograde transsynaptic degeneration in the human visual system

Abstract: DTI markers of RTD are apparent 3 months from the time of injury. This represents the earliest noninvasive evidence of RTD in any species. Furthermore, these measures associate with measures of visual impairment. DTI measures offer a reproducible, noninvasive, and sensitive method of investigating RTD and its role in visual impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This makes intuitive sense, as retrograde degeneration in humans is well underway and clearly evidenced by structural changes relatively early in the chronic period. 25 , 28 , 34 , 57 Intervening in the subacute period may catch the visual system in a state where degeneration is not yet complete. Therefore, we posit that future studies should investigate if early intervention in acute and sub-acute CB populations can slow the rate or magnitude of degeneration, keeping LI max closer to zero for longer and thus, further improving the potential for training induced visual recovery once participants reach the chronic poststroke period.…”
Section: Discussionmentioning
confidence: 99%
“…This makes intuitive sense, as retrograde degeneration in humans is well underway and clearly evidenced by structural changes relatively early in the chronic period. 25 , 28 , 34 , 57 Intervening in the subacute period may catch the visual system in a state where degeneration is not yet complete. Therefore, we posit that future studies should investigate if early intervention in acute and sub-acute CB populations can slow the rate or magnitude of degeneration, keeping LI max closer to zero for longer and thus, further improving the potential for training induced visual recovery once participants reach the chronic poststroke period.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, microstructural damage of the cortico-striatal and thalamo-cortical projections may result from mechanisms of retrograde [ 25 ] and anterograde [ 26 ] transneuronal axonal degeneration, respectively, caused by primary neurodegeneration of intermediate relay stations—mainly the substantia nigra—within the cortico-striatal-thalamo-cortical motor loop. In accordance with this speculation, similar alterations of DTI metrics have been demonstrated in the frontal WM of Parkinson’s disease (PD) patients [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the optic radiations or primary visual cortex (V1) causes blindness in the contralesional visual hemifield of both eyes. Degeneration of ganglion cells in the retina has been detected following occipital lobe damage in postmortem studies [1 -3] and in in vivo studies [4][5][6] of monkeys, cats, and humans. Prior cross-sectional studies have shown that the distribution of retinal ganglion cell degeneration years after a stroke is spatially correlated with the persistent visual field defect [7][8][9].…”
Section: Introductionmentioning
confidence: 99%